The Significance of Demons in the Consultation Room and Children's Psychological Trauma - Su-Chen Hung (National Taipei University of Education, 2017)
The purpose of this article is to elucidate the possible implications of related trauma and demon phenomena manifested by children in the consultation room by using the con-cepts of father complex, archetype, the collective unconscious in Jungian psychology and the theoretical framework of object relations. Children in the cases in this article have all lost their fathers and started receiving treatment after having a traumatic response. When trauma occurs in children, it manifests as internal or external symptoms; the traumatic response to bereavement in the two cases in the article was presented as demons and be-ing overly attached to his/her mother. Thus, the topic of demons was touched upon during their treatment. While they originally projected fear of ghosts or love for ghost films as a defense mechanism for the pain of bereavement, after analysis and explanation, they were able to begin dialogue about their loss. To children, the significance of imagining demons lies in their introjection of their mother's inability to mourn their father's death. They use their fear of demons as an excuse to accompany their mother while preserving internally the object of great father and pro-jecting the object of bad father in order to display the father complex. Children internalize their father figure again by understanding their demon phenomenon.